Involuntary Psychiatric Treatment and Other Coercive Behavioral Interventions as Criminal Sanctions: Reflections on Vitek v. Jones - Carl J. Circo (Washington University Law Quarterly, 1981)
This Article inquires into the substantive limits on the power of government to impose coercive behavioral interventions on criminal offenders solely because of a criminal conviction and sentence.
Keywords: Administration of criminal justice; Due process of law; Mental health services; Prisoners; United States